Recycling of catalyst coating film components

JP2026534096APending Publication Date: 2026-10-14JOHNSON MATTHEY PLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026516241
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-18
Filing Date
2024-06-24
Publication Date
2026-10-14

Smart Images

  • Figure 2026534096000001_ABST
    Figure 2026534096000001_ABST
Patent Text Reader

Abstract

A method for recycling a spent catalyst coating material comprising an ionomer, at least one catalyst comprising platinum, palladium and / or ruthenium, and at least one catalyst comprising iridium binary oxide, the method comprising: (a) treating the spent catalyst coating material with a heated solution comprising an acid and an oxidizing agent, wherein platinum, palladium and / or ruthenium are leached from the spent catalyst coating material into the solution and separated from the remaining solid components of the spent catalyst coating material; (b) treating the spent catalyst coating material with a solvent to disperse the ionomer and recover the dispersion of the ionomer, wherein the dispersion of the ionomer is performed before or after the leaching of platinum, palladium and / or ruthenium in step (a); and (c) after the recovery of platinum, palladium and / or ruthenium and the ionomer in steps (a) and (b), treating the residual spent catalyst coating material by one of three specific processes to extract iridium.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present specification relates to a method for recycling components of catalyst coated membranes, such as those used in fuel cells and hydrogen-generating water electrolyzers.

BACKGROUND ART

[0002] As investments are made in the global hydrogen economy, the production of fuel cells and hydrogen-generating water electrolyzers is expected to grow rapidly. A catalyst coated membrane (CCM) is a major functional component of both fuel cells and electrolyzers. Such CCMs generally comprise an electrically conductive polymer membrane coated on both sides by catalyst-containing layers. CCMs are configured to drive oxidation and reduction reactions and support proton and electron transport, and these processes are required for fuel cell and electrolyzer technologies to function.

[0003] While variations exist in the materials and configurations of CCM components according to functional performance requirements in end-use applications, they generally contain several valuable components including one or more platinum group metal (PGM) catalysts and one or more proton-conductive polymers.

[0004] Typically, the membrane is formed from one or more ionomers such as perfluorosulfonic-acid (PFSA) ionomers. Ionomers may also be provided in one or both of the catalyst layers. The ionomer in the catalyst layer may be the same as or different from the ionomer in the main membrane component and / or in the other catalyst layer.

[0005] The CCM may contain two different catalysts, one for driving an oxidation reaction on one side of the CCM and the other for driving a reduction reaction on the other side of the CCM. The CCM may also contain a recombination catalyst provided to catalyze the recombination of hydrogen and oxygen to form water, reducing the amount of hydrogen passing through the membrane and mixing with oxygen to form a potentially explosive mixture. The CCM may also contain a metal oxide (e.g., CeO2) as a peroxide scavenger.

[0006] CCM catalysts can be based on platinum group metals such as platinum, ruthenium, iridium, palladium, or mixtures thereof. Platinum group metals may be provided in elemental (metallic) form, compound form (e.g., oxides such as iridium oxide catalysts), or PGM-based metal alloys (e.g., PtCo). Furthermore, the PGM catalyst material may be supported on a substrate material (e.g., carbon such as a platinum-supported carbon catalyst or PtCo-supported carbon containing carbon particles on which platinum is arranged).

[0007] The catalyst coating (CCM) can also be provided in combination with additional functional layers to form a membrane electrode assembly (MEA). Such an MEA may have, for example, 3, 5, or 7 layers.

[0008] With the increase in CCM production for fuel cells and electrolytic cells, there is also a corresponding increase in CCM waste material, including large amounts of scrap material generated during CCM production (e.g., due to quality control failures), and an increase in end-of-life (EoL) CCM. Since CCM contains several rare and / or valuable components, including platinum group metals (particularly Pt, Pd, Ir, and Ru) and ionomers (in both membrane and catalyst layers), there is a growing demand for methods to recycle such components from waste CCM material.

[0009] One current method for recovering PGMs from production scrap and end-of-life CCM materials involves incineration. The incineration process produces PGM-rich ash (typically Pt and Ir) that is processed through conventional PGM refining routes. However, the incineration process releases harmful and toxic gases such as CO2 and HF from the polymers that are part of the membrane. Both of these gases have adverse effects as they pollute the atmosphere, increase the greenhouse effect, and / or have harmful effects on human health. Therefore, cleaner methods are needed to reduce or eliminate the emissions of these gases.

[0010] In addition to the above, incineration methods destroy ionomer components, which are of equally important value. Therefore, it is desirable to provide a process that can recover both PGMs and ionomer components, as well as a process that is cleaner, safer, and more environmentally friendly. Processes for recovering perfluorosulfonic acid ionomers are known. See, for example, International Publication No. WO2016 / 156815 and U.S. Patent No. 7255798. Furthermore, processes for recovering individual PGM catalyst components are known. See, for example, U.S. Patent No. 7709135. However, in order to enable fuel cells and electrolytic cells to become more sustainable technologies, there is a need for commercially viable and environmentally friendly routes for recovering, separating, and recycling both PGMs and ionomer components from waste CCM materials, including production scrap and end-of-life materials.

[0011] The purpose of this specification is to address this problem. [Overview of the project]

[0012] This specification relates, in particular, to the recycling of spent catalyst coating materials comprising an ionomer, at least one catalyst comprising platinum, palladium, and / or ruthenium, and at least one catalyst comprising iridium binary oxides such as iridium tantalum oxide (IrTaOx) and / or iridium ruthenium oxide (IrRuOx). Iridium binary oxides are, as is well known, stable catalysts and therefore resistant to simple acid dissolution and purification methods that can be used for other catalyst materials, thus presenting specific challenges. This specification provides a method for recovering all platinum group metal components and ionomer components from spent catalyst coating materials comprising iridium binary oxides such as iridium tantalum oxide (IrTaOx) and / or iridium ruthenium oxide (IrRuOx).

[0013] This specification provides a method for recycling a waste catalyst coating material comprising an ionomer, at least one catalyst comprising platinum, palladium and / or ruthenium, and at least one catalyst comprising iridium binary oxide (e.g., IrTaOx and / or IrRuOx), wherein the method is as follows: (a) A treatment in which the spent catalyst coating material is treated with a solution containing an acid and an oxidizing agent, wherein platinum, palladium and / or ruthenium are leached from the spent catalyst coating material into the solution, and the solution is separated from the remaining solid components of the spent catalyst coating material. (b) Treatment of the spent catalyst coating material with a solvent to disperse the ionomer, and recovery of the ionomer dispersion, wherein the dispersion of the ionomer is performed before or after the leaching of platinum, palladium, and / or ruthenium in step (a), (c) After recovering platinum, palladium and / or ruthenium and ionomer in steps (a) and (b), the process includes treating the residual waste catalyst coating material by one of the following three processes to extract iridium, the three processes being: (i) After leaching of platinum, palladium and / or ruthenium and dispersion and recovery of ionomers, iridium is directly recovered as a solid iridium binary oxide catalyst material, (ii) subjecting iridium binary oxide to a peroxide melting process, wherein the iridium binary oxide material is mixed with an alkali melting flux, heated in a furnace, and then subjected to acid dissolution to recover the iridium in the solution. (iii) to separate the platinum group metals, iridium binary oxide is subjected to one or more dry metallurgical processes including smelting, followed by acid dissolution of the platinum group metals, and a series of wet metallurgical processes for separating and purifying the individual platinum group metals, including iridium.

[0014] This method is based on the recognition that the iridium binary oxide component is the most stable component and therefore advantageous to recover after the recovery of the platinum, palladium, and / or ruthenium components and the ionomer component. In this regard, it has been found that the iridium binary oxide component does not leach out by the leaching processes that can be used to recover the platinum, palladium, and / or ruthenium components. Furthermore, it has been found that the iridium binary oxide component, after being subjected to the oxidizing acid leaching conditions used to recover the platinum, palladium, and / or ruthenium components, meets the specification requirements for reuse in fuel cell applications. Therefore, according to route (c)(i) of this method, it is possible to recover the iridium binary oxide catalyst material for direct reuse without requiring metal separation, purification, and resynthesis of a new iridium binary oxide catalyst material.

[0015] As an alternative to the direct recovery and reuse of iridium binary oxide catalyst materials, it is possible to recover the iridium component of binary oxide materials. However, although reductive acid leaching can be used to recover iridium from non-binary iridium oxide catalyst materials, such reductive acid leaching processes do not yield a high iridium recovery yield for iridium binary oxide catalyst materials. According to this specification, in addition to the direct recovery route (c)(i), two alternative methods are available.

[0016] According to Route (c)(ii), iridium binary oxide is subjected to a peroxide melting process, in which the iridium binary oxide material is mixed with an alkali melting flux, heated in a furnace, and then subjected to acid dissolution to recover the iridium in the solution. The peroxide melting process is already currently performed by analytical laboratories for the analysis of iridium binary oxide material. In this specification, this known method is moved from the context of analytical analysis to a recycling method for recovering iridium (and optionally other metallic components of the binary oxide) from waste iridium binary oxide material generated after the separation of platinum and ionomer components.

[0017] Alternatively, according to route (c)(iii), iridium binary oxide can be fed into a PGM refining circuit, where the material is subjected to one or more dry metallurgical processes, including smelting, to separate the platinum group metals, followed by acid dissolution of the platinum group metals, and a series of wet metallurgical processes to separate and purify the individual platinum group metals, including iridium. Optionally, the residual iridium binary oxide-containing material may be ashed to remove residual ionomers before entering the refining circuit. Advantageously, this approach allows for the separation and purification of iridium (and optionally other metallic components of the binary oxide) from waste iridium binary oxide material generated after the separation of platinum and ionomer components, using existing PGM refining processes. However, compared to the more customized recycling approaches of routes c(i) and c(ii), the recycling time may be longer.

[0018] Further details of this method are provided in the detailed description below. [Brief explanation of the drawing]

[0019] For a better understanding of the present invention and to illustrate how it can be implemented, certain embodiments of the present invention are described hereby by reference only to the accompanying drawings. [Figure 1] This specification shows the CCM recycling process. [Figure 2]This is a diagram showing FTIR data for a fluorinated polymer membrane material, a fluorinated polymer salt material formed after treatment in water and a base, and a fluorinated polymer salt material formed after treatment in water and a base and subsequently washed with water. [Figure 3] This is a diagram showing an example of process steps (before autoclaving) comprising refluxing a fluorinated polymer membrane in a basic LiOH solution to form a fluorinated polymer salt without dispersing the membrane, followed by washing with water. [Figure 4] This is a photograph showing the membrane before (left side) and after (right side) the process steps of refluxing the membrane in a basic LiOH solution and washing with water. [Figure 5] A further step of subjecting the membrane to an autoclave treatment following the treatment process shown in FIG. 3 to disperse the membrane in water is shown. [Figure 6] A further step of ion exchange (after autoclaving) for converting the dispersed polymer salt back to the protonated acid form is shown. MODE FOR CARRYING OUT THE INVENTION

[0020] As described in the Summary of the Invention section and shown in FIG. 1, according to one aspect of the present specification, there is provided a method for recycling a spent catalyst-coated membrane material comprising an ionomer, at least one catalyst comprising platinum, palladium and / or ruthenium, and at least one catalyst comprising an iridium binary oxide (e.g., IrTaOx and / or IrRuOx), the method comprising: (a) treating the spent catalyst-coated membrane material with a solution comprising an acid and an oxidizing agent, wherein platinum, palladium and / or ruthenium is leached from the spent catalyst-coated membrane material into the solution, and the solution is separated from the remaining solid components of the spent catalyst-coated membrane material; (b) treating the spent catalyst-coated membrane material with a solvent to disperse the ionomer and recover an ionomer dispersion, wherein the dispersion of the ionomer is performed before or after the leaching of platinum, palladium and / or ruthenium in step (a); and (c) after recovering platinum, palladium and / or ruthenium and the ionomer in steps (a) and (b), treating the residual spent catalyst coating material to extract iridium by one of the following three processes, wherein the three processes are: (i) directly recovering iridium as a solid iridium binary oxide catalyst material after leaching of platinum, palladium and / or ruthenium as well as dispersion and recovery of the ionomer; (ii) subjecting the iridium binary oxide to a peroxide melting process, wherein the iridium binary oxide material is mixed with an alkaline melting flux, heated in a furnace, and then subjected to acid dissolution to recover iridium in the solution; (iii) subjecting the iridium binary oxide to one or more pyrometallurgical processes including smelting to separate platinum group metals, followed by acid dissolution of the platinum group metals and a series of hydrometallurgical processes for separating and purifying individual platinum group metals including iridium.

[0021] In step (a), the acid used for leaching platinum, palladium, and / or ruthenium may be hydrochloric acid. The oxidizing agent used for leaching may be chlorate, chlorine gas, or hydrogen peroxide. The oxidant concentration may be at least 0.001, 0.005, or 0.01 mol / L; 1, 0.5, or 0.10 mol / L or less; or within a range defined by any combination of the aforementioned lower and upper limit values (for example, within the range of 0.01 to 0.10 mol / L). The acid concentration may be 4M, 5M, or 5.5M or more; 7M or less, 6.5M or less, or 6M or less; or within a range defined by any combination of the aforementioned lower and upper limit values. The leaching solution may optionally be heated to a temperature within a range defined by at least 50°C, 60°C, or 70°C; 160°C, 100°C, or 90°C or less; or any combination of the aforementioned lower and upper limit values, and when the solution is heated above 100°C, this is carried out in a pressurized vessel.

[0022] These leaching conditions were found to be effective for leaching platinum, palladium, and / or ruthenium catalyst materials. Furthermore, these leaching conditions do not leach any iridium binary oxides. The effect of the leaching process on the microstructure, crystal structure, and composition of iridium binary oxides is minimal, and the iridium binary oxides maintain a form that can be directly reused to create new CCM components.

[0023] As specified in step (b) of this method, the ionomer is dispersed either before or after the aforementioned leaching step, and the resulting ionomer dispersion is separated from the remaining waste catalyst coating material containing iridium binary oxide. The solvent used to disperse the ionomer may be selected from water, a basic aqueous solution, an organic solvent, an alcohol, or a mixture of alcohol and water. In the ionomer dispersion step, the solvent may be heated to a temperature within the range defined by at least 150°C, 180°C, 200°C, 220°C, 230°C, or 240°C; 400°C, 300°C, 275°C, or 250°C or less; or any combination of the aforementioned lower and upper limits. Heating may be carried out in an autoclave.

[0024] According to a particular preferred method, the ionomer can be converted to a salt form by treating it with a base (e.g., an aqueous solution of a metal hydroxide or ammonium hydroxide, e.g., LiOH). This treatment can be performed on the solid ionomer material without dispersing it, as long as the material is not heated to the above temperature for the dispersion step. The ionomer can then be dispersed in the solvent by removing the excess base and replacing it with another solvent (e.g., water), and then heating in an autoclave as described above. Alternatively, the ionomer can be dispersed by heating using a basic aqueous solution as the solvent. However, one advantage of first converting the solid ionomer to a salt form and then subsequently dispersing the ionomer in a different solvent is that the excess base can be removed before dispersion of the ionomer so that the ionomer dispersion is not contaminated with excess base.

[0025] Once the ionomer and the platinum, palladium, and / or ruthenium catalyst materials are removed, the residual waste catalyst coating material contains iridium binary oxide and potentially other components, such as carbon and / or film reinforcing materials. Advantageously, the iridium binary oxide is separated from any other residual components before further processing. For example, a slurry of the residual waste material can be formed and filtered to separate the solid components according to their different particle sizes. The recovered iridium binary oxide can then be washed and dried to prepare it for reuse in new catalyst ink formulations.

[0026] While it is known that iridium binary oxide materials can be directly recovered in a form acceptable for reuse in this manner, if the recovered binary oxide material does not meet the specifications for a particular application, or if the recovery of individual metal components is desirable, the individual metal components can be recovered and purified separately instead. According to route (c)(ii) of this method, the iridium binary oxide is subjected to a peroxide melting process, where the iridium binary oxide material is mixed with an alkali melting flux, heated in a furnace, and then subjected to acid dissolution to recover the iridium in the solution. Other metals in the binary oxide (e.g., Ta or Ru) can also be recovered via this route.

[0027] Alternatively, iridium can be recovered via route (c)(iii), which involves feeding iridium binary oxide to one or more dry metallurgical processes including smelting, followed by acid dissolution of the platinum group metals, and a series of wet metallurgical processes for separating and purifying the individual platinum group metals, including iridium, in order to separate the platinum group metals. Other metals in the binary oxide (e.g., Ta or Ru) can also be recovered via this route.

[0028] The methods described herein can be applied to spent catalyst coating materials in the form of catalyst coating films or ionomer-containing catalyst materials separated from ionomer films. [Examples]

[0029] Platinum Recovery CCM-HCl / chloride leaching A method has been developed to leach PGMs from CCM manufacturing scrap. The recovered PGM material is then purified using existing PGM purification processes. Such processes have strict limitations on the fluorine content (<1%) of the PGM material introduced into the PGM purification process. Since CCM is made primarily from fluoropolymers, this has been identified as a potential problem for leaching PGMs from waste CCM material. The leaching process of the present invention is such that PGMs can be leached without introducing a significant amount of fluorine into the leachate.

[0030] Pt was dissolved from CCM using an HCl / chlorate solution. Ir was in oxide form in CCM, and no significant amount of Ir leached out, allowing for the separation of Pt and Ir. Chlorates were introduced in the form of a sodium chlorate solution added using a peristaltic pump.

[0031] A container was placed with fuel cell carbon capture material (CCM) cut into approximately 2cm x 3cm pieces. 400mL of 6M HCl (a solution prepared from concentrated HCl and distilled H2O) was added to the flask, and the stirring speed was set to 250rpm. The reaction mixture was heated to 70°C. A slight yellow color was observed in the solution during heating.

[0032] 4 mL of NaClO3 solution (450 g / L) was added at a rate of approximately 0.09 mL / min. After the addition of the NaClO3 solution was complete, the reaction mixture was cooled to room temperature. The reaction mixture was filtered through 0.45 μm filter paper. This yielded a yellow solution (365 mL). The liquid was collected, and the remaining CCM fragments were washed with distilled H2O (86 mL). The CCM fragments were removed and dried in the air overnight on a watch glass.

[0033] IC / ICP analysis showed that under the leaching conditions, Ir did not leach to a significant extent. In contrast, approximately 100% of Pt leached into the leachate. The leachate also showed undetectable amounts of fluoride, indicating that the leaching conditions did not destroy the ionomer in the CCM.

[0034] Therefore, this approach has been shown to be usable to recover Pt from waste CCM material without damaging the ionomer material of the CCM or introducing fluorine into the Pt treatment stream for subsequent Pt purification. It has also been shown that Pt can be leached from waste CCM material without also leaching iridium, and thus Pt and Ir can be separated and recovered for reuse. Thus, it is possible to recover Pt, Ir, and ionomer components (and optionally ruthenium or palladium (if present)) using this approach.

[0035] Ionomer recovery The perfluorosulfonic acid ionomer film fragments were cut into pieces small enough to fit in the container. 6.0 g of anhydrous LiOH and 250 g of water were weighed, and the LiOH was dissolved in the water. The film fragments were submerged in the LiOH solution and heated under reflux for 1 hour. The resulting mixture was washed with 4 × 100 mL of water. The remaining water was decanted to leave the (moist) film fragments. 250 g of water was weighed and added to the (moist) film fragments, and heated under reflux for 1 hour. The water was then removed by decantation, and the solid product was dried under vacuum.

[0036] Figure 2 shows FTIR data indicating salt formation. FTIR data was collected for the untreated fluorinated polymer film material 301, the fluorinated polymer salt material 303 formed after treatment in an aqueous LiOH solution, and the fluorinated polymer salt material formed after treatment in an aqueous LiOH solution, followed by water washing 304.

[0037] Figure 3 shows an example of the process steps (before autoclaving). The film on a roll was cut, and then further cut or folded to size. The film was brownish in color, as shown in the figure. The film was then refluxed in a lithium hydroxide solution, at which point it became colorless and was converted to a salt form, as confirmed by spectroscopic analysis. The conversion was achieved without dispersing the film, and the film remained in a solid, non-disperse form.

[0038] It should be noted that a change in film color does not necessarily indicate a chemical change, and films can have different colors. However, in the exemplary examples, the chemical change of the polymer from the protonated form to the salt form was accompanied by a corresponding color change, as shown in the figure.

[0039] In the final step before autoclaving, as shown in Figure 3, the solid polymer salt film material was washed with water to remove all residual LiOH solution. Figure 4 shows photographs of the film before (left) and after (right) the process of refluxing the film in a basic LiOH solution and washing it with water, illustrating the change in film color from brown to colorless, and the fact that the film remains in a solid, non-dispersed state. Spectroscopic analysis confirmed that the colorless film was in salt form.

[0040] Figure 5 shows a further step of autoclaving the membrane following the processing steps shown in Figure 3, in order to disperse the membrane in water. A colorless solid, undispersed polymer salt membrane was autoclaved in water under nitrogen at 250°C and a pressure of 40 bar / 4000 kPa. This yielded a (non-basic) aqueous dispersion of the polymer salt.

[0041] Figure 6 shows a further ion exchange step (after autoclaving) to convert the dispersed polymer salt back into a protonated acid form. An ion exchange column containing Amberlyst® 15(H) resin was used in this process step. The dispersion of (protonated)fluorinated polymer may be reused to produce a new membrane or may be dried and stored for future use.

[0042] Iridium recovery IrTaOx is found in certain catalyst powders for fuel cell applications to improve system stability. However, oxidation leaching experiments using peroxides and NaClO3 showed a 0% Ir recovery rate when IrTaOx leached out. This suggests the possibility of direct recovery and reuse of IrTaOx as a catalyst powder.

[0043] To understand whether the leaching residue can be directly recycled, the powder was characterized and compared to the starting material to examine how the leaching conditions affected the material structure. If the structure does not change significantly, it can be recycled by mixing it with new material, at an optional rate.

[0044] To test whether iridium binary oxide can be directly recycled and reused as a catalyst material in fuel cell catalyst coatings using the methods described herein, samples of the material were subjected to an oxidizing acid leaching process similar to those used to recover platinum (or alternatively, palladium or ruthenium). Samples of the solid iridium binary oxide material recovered after the platinum leaching process were then analyzed using SEM, XRD, ICP, and nitrogen BET surface area measurement to determine whether they met the specifications for reuse as a catalyst in new fuel cell catalyst coatings. To determine if there were any variations according to the specific leaching process used to recover platinum, one set of samples was subjected to HCl acid leaching using a peroxide as the oxidizing agent, and another set of samples was subjected to HCl acid leaching using NaClO3 as the oxidizing agent.

[0045] SEM analysis SEM images were taken of the iridium tantalum oxide starting material. Furthermore, SEM images were taken of the iridium tantalum oxide after HCl acid leaching using H2O2 as the oxidizing agent. And then, SEM images were taken of the iridium tantalum oxide after HCl acid leaching using NaClO3 as the oxidizing agent.

[0046] Visual inspection of SEM images suggested that when NaClO3 was used as the oxidizing agent, the particles were more pulverized and / or had smaller particle sizes. This suggests that NaClO3 is a harsher oxidizing agent than peroxide. Images of the starting material compared to samples leached with peroxide appeared to have a more similar structure, suggesting that peroxide does not damage the structure as much and may be suitable for direct recycling.

[0047] After analyzing the SEM data, visually, the SEM analysis indicated that this sample had more differences compared to the starting material, and therefore was more likely to benefit from the data collected in QC analysis, thus determining that more IrTaOx would leach using HCl / NaClO3. The use of NaClO3 as the oxidizing agent is also more similar to the conditions under which it is used with Cl2(g), which is more likely to be used as an oxidizing agent when the process is performed on a larger scale.

[0048] XRD analysis XRD analysis of the NaClO3 leached sample revealed that the phase was an Ir / Ta oxide, and the single-crystal phase determined by XRD falls within the product specifications in terms of the average crystallite size and composition of the IrTaOx catalyst material.

[0049] ICP analysis The leached residue was sent for ICP analysis, and the results showed that the Ir and Ta content were within the specifications for the IrTaOx catalyst material. Impurities in the sample were also within the specification limits. The Fe content, like the Cl content, was below a specific limit. Overall, the leached sample met the specifications for the ICP results.

[0050] Nitrogen BET Analysis The BET surface area was measured and also fell within the specification limits of the IrTaOx catalyst material; therefore, the leached material also met this criterion.

[0051] conclusion Trials using IrTaOx powder demonstrated that the material still met product specifications even after the catalyst was exposed to a Pt leaching process. The results indicate that a direct recycling route for iridium binary oxide materials is feasible.

[0052] Peroxide melting As an alternative to the direct recovery and reuse of iridium binary oxide catalyst materials, iridium and other metals can be recovered using a peroxide melting process. Peroxide melting has already been used to process samples of iridium binary oxide catalyst powder for analysis. The iridium binary oxide catalyst powder is mixed with an alkaline melting flux, heated in a furnace, and then subjected to acid dissolution to recover the iridium in the solution. Other metals in the binary oxide (e.g., Ta or Ru) can also be recovered via this route. For example, iridium binary oxide can be mixed with sodium peroxide, heated in a furnace, and then acid leached. An example of such a method for processing iridium is described in the paper "Chemical Dissolution of Iridium Powder Using Alkali Fusion Followed by High-Temperature Leaching" by Jaeryeong Lee and Youngjin Kim, published in Materials Transactions, Vol. 52 (2011), No. 11. This paper describes the dissolution of iridium by alkaline fusion treatment using Na2O2, followed by leaching in an HCl solution. It is stated that alkaline fusion using Na2O2 readily oxidizes Ir to IrO2, which is converted to a highly oxidized state through Na-Ir-O bonding at 600°C for 4 hours. From the molten mixture, Ir can be completely leached at 130°C using an HCl solution with a molar ratio of 1:2.0 (Ir:Na2O2In) and a concentration greater than 3M. Furthermore, leaching at 130°C with 3M HCl can completely dissolve Ir from the mixture molten at 600°C, regardless of the molar ratio of Na2O2. Ir can also be completely dissolved at temperatures below 70°C when the molten mixture has a 1:2.0 ratio. According to this specification, the corresponding process can be used to recover iridium from iridium binary oxide catalyst powder used in CCM. However, in the case of IrTaOx catalysts, the use of HF in addition to HCl is required to support the separation of tantalum.

[0053] Large-scale melting is already being used to process the material. Therefore, this represents a viable alternative route for recovering iridium (as well as other metals in binary oxides).

[0054] Dry metallurgy route As an alternative to using the peroxide melting method described above, iridium binary oxide material can be fed into an existing PGM purification process that includes dry metallurgy treatment followed by acid dissolution and wet metallurgy for the separation and purification of PGMs. The dry metallurgy route may require an ashing step to burn off residual ionomers before entering the existing purification circuit in order to proceed to the existing process for purifying the PGM feedstock. For example, the material can be smelted in a reverberatory furnace at over 1200°C for about 12 hours to separate nonmetallic components and produce an iron-based feedstock containing PGMs. The bullion feedstock is then subjected to acid leaching to concentrate the PGMs in solution, followed by a series of solvent extraction, evaporation, precipitation, and filtration steps to separate and purify the PGMs.

[0055] summary This specification provides a flow sheet for recovering Pt (or alternatively Pd or Ru), ionomers, and IrTaOx (and alternative Ir binary oxides) from fuel cell membrane electrode assemblies (MEAs) and catalyst coatings (CCMs). Pt can be recovered by oxidative leaching using HCl as the acid and chlorine, hydrogen peroxide, or sodium chlorate as the oxidizing agent. The remaining residue then undergoes an ionomer dispersion process, but it should be noted that the recovery of the ionomer and Pt can occur in either order. The remaining residue mainly consists of alternative binary oxides such as IrTa oxide or IrRu oxide and some carbon. This can then be subject to a choice of recovery method. One route is to employ separation techniques to directly recover IrTaOx as catalyst powder and prepare it for reuse. Alternatively, the residue can undergo peroxide melting processes, which are currently being performed by analytical laboratories to analyze this material; barium peroxide melting is already being performed on a large scale. This allows Ir to enter the solution, and then it can be processed using known techniques to purify the material. Another option is to place this material into an existing smelting circuit and have it proceed to the dry metallurgy route. The residue can be ashed before entering the purifying circuit.

[0056] Therefore, this specification enables the recovery of all PGMs and ionomers in waste CCM materials containing iridium binary oxides such as IrTaOx.

[0057] Although the present invention has been specifically illustrated and described with reference to certain examples, it will be understood by those skilled in the art that various modifications of form and detail can be made without departing from the scope of the invention as defined by the appended claims.

Claims

1. A method for recycling a waste catalyst coating material comprising an ionomer, at least one catalyst containing platinum, palladium and / or ruthenium, and at least one catalyst containing iridium binary oxide, (a) The spent catalyst coating material is treated with a solution containing an acid and an oxidizing agent, wherein platinum, palladium and / or ruthenium are leached from the spent catalyst coating material into the solution, and the solution is separated from the remaining solid components of the spent catalyst coating material. (b) Treating the waste catalyst coating material with a solvent to disperse the ionomer and recovering the ionomer dispersion, wherein the dispersion of the ionomer is performed before or after the leaching of platinum, palladium, and / or ruthenium in step (a), (c) A method comprising, after the recovery of the platinum, palladium and / or ruthenium and the ionomer in steps (a) and (b), treating the residual waste catalyst coating material by one of the following three processes to extract iridium, wherein the three processes are: (i) After the leaching of platinum, palladium and / or ruthenium and the dispersion and recovery of the ionomer, the iridium is directly recovered as a solid iridium binary oxide catalyst material. (ii) subjecting the iridium binary oxide to a peroxide melting process, wherein the iridium binary oxide material is mixed with an alkali melting flux, heated in a furnace, and then subjected to acid dissolution to recover the iridium in the solution. (iii) To separate the platinum group metals, the iridium binary oxide is subjected to one or more dry metallurgical processes including smelting, followed by acid dissolution of the platinum group metals, and a series of wet metallurgical processes for separating and purifying the individual platinum group metals, including iridium, by processing the residual waste catalyst coating material to extract iridium. A method that includes this.

2. The method according to claim 1, wherein the iridium binary oxide is iridium tantalum oxide or iridium ruthenium oxide.

3. The method according to claim 1 or 2, wherein in step (a), the acid used for the leaching of platinum, palladium, and / or ruthenium is hydrochloric acid.

4. The method according to any one of claims 1 to 3, wherein the oxidizing agent used for the leaching of platinum, palladium and / or ruthenium in step (a) comprises a chlorate, chlorine gas, or hydrogen peroxide.

5. The method according to any one of claims 1 to 4, wherein in step (a), the solution for leaching platinum, palladium and / or ruthenium has an oxidizing agent concentration of at least 0.001, 0.005, or 0.01 mol / L; 1, 0.5, or 0.10 mol / L or less; or within the range defined by any combination of the aforementioned lower and upper limits.

6. The method according to any one of claims 1 to 5, wherein in step (a), the solution for leaching platinum, palladium, and / or ruthenium has an acid concentration of 4 M, 5 M, or 5.5 M or more; 7 M or less, 6.5 M or less, or 6 M or less; or within the range defined by any combination of the aforementioned lower and upper limits.

7. The method according to any one of claims 1 to 6, wherein in step (a), the solution used for the leaching of platinum, palladium, and / or ruthenium is optionally heated to a temperature within the range defined by at least 50°C, 60°C, or 70°C; 160°C, 100°C, or 90°C or less; or any combination of the aforementioned lower and upper limits, and if the solution is heated above 100°C, this is done in a pressurized vessel.

8. The method according to any one of claims 1 to 7, wherein the solvent used to disperse the ionomer in step (b) is selected from water, an aqueous basic solution, an organic solvent, an alcohol, or a mixture of alcohol and water.

9. The method according to any one of claims 1 to 8, wherein in step (b), the solvent used to disperse the ionomer is heated to a temperature within the range defined by at least 150°C, 180°C, 200°C, 220°C, 230°C, or 240°C; 400°C, 300°C, 275°C, or 250°C or less; or any combination of the aforementioned lower and upper limits.

10. The method according to any one of claims 1 to 9, wherein in step (b), before dispersing the ionomer in the solvent, the ionomer is treated with a base to convert the ionomer into a salt form.

11. The method according to any one of claims 1 to 10, wherein in step (c), the solid iridium binary oxide catalyst material is separated from other residual components of the waste catalyst coating material by forming a particle suspension and filtration for separating components according to particle size.

12. The method according to any one of claims 1 to 11, wherein, in step (c), after the leaching of platinum, palladium and / or ruthenium and the dispersion and recovery of the ionomer, the iridium is recovered via a route (i) in which the iridium is directly recovered as a solid iridium binary oxide catalyst material.

13. The method according to any one of claims 1 to 11, wherein in step (c), the iridium binary oxide material is mixed with an alkali melting flux, heated in a furnace, and then subjected to acid dissolution to recover the iridium in the solution, and the iridium is recovered via a route (ii) through which the iridium binary oxide is supplied.

14. The method according to any one of claims 1 to 11, wherein in step (c), the iridium is recovered via a route (iii) through which the iridium binary oxide is supplied to one or more dry metallurgical processes including smelting for the separation of the platinum group metals, followed by acid dissolution of the platinum group metals, and a series of wet metallurgical processes for separating and purifying the individual platinum group metals, including iridium.

15. The method according to any one of claims 1 to 14, wherein the waste catalyst coating material is one or more ionomer-containing catalyst materials separated from a catalyst coating film or an ionomer film.